2014
DOI: 10.1080/01496395.2014.906464
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Percolation Threshold for the Oxalic, Tartaric, and Lactic Acids Transport through Polymer Inclusion Membranes with 1-Alkylimidazoles as a Carrier

Abstract: As part of this work the study of transport of organic acids, namely oxalic, tartaric, and lactic acids through polymer inclusion membrane were carried out. As a polymer matrix cellulose triacetate (CTA) and as a carrier 1-alkiloimidazole (IMI-n, n = 10, 11, 12, 14) were used. The aim of this study was to determine the effect of the qualitative and quantitative composition of the polymer inclusion membrane on the transport rate of selected organic acids. On the basis of the obtained results and percolation the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…She demonstrated that an increase in the carrier concentration results in an increase in the polymer membrane viscosity, and this forms an additional barrier in a diffusion mass transport through the PIM. Similar observations were made by Przewoźna et al [18], who found that too high amount of the carrier could result in its secretion on the membrane surface, also forming an additional barrier to the mass transport through PIM.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…She demonstrated that an increase in the carrier concentration results in an increase in the polymer membrane viscosity, and this forms an additional barrier in a diffusion mass transport through the PIM. Similar observations were made by Przewoźna et al [18], who found that too high amount of the carrier could result in its secretion on the membrane surface, also forming an additional barrier to the mass transport through PIM.…”
Section: Introductionsupporting
confidence: 86%
“…In recent years, the phosphonium ionic liquids have attracted a significant interest of researchers studying solvent extraction [11][12][13][14] and membrane techniques [15][16][17][18], due to their properties.…”
Section: Introductionmentioning
confidence: 99%
“…Alkyl derivatives of imidazoles, entering the hydration sphere of ions—such as copper(II), nickel(II), or cobalt(II)—create complexes with the general form of MCl 2 L 2 , where L is an organic ligand [ 51 , 52 ]. Because of these properties, azoles, imidazoles [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], and triazoles [ 59 , 60 ] in particular, are used as extractants or carriers of ions for selective extraction and separation of not only transition group metals but also organic acids [ 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…noble metals, actinides, lanthanides, and heavy metals, such as zinc, iron, cadmium, copper, nickel, lead, chromium, mercury, cobalt, and manganese . Also, PIMs were applied for the transport of such organic compounds as oxalic, tartaric, lactic or citric acid …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][6][7][8][9][10][11][12][18][19][20][21][22][23] Also, PIMs were applied for the transport of such organic compounds as oxalic, tartaric, lactic or citric acid. [24][25][26] Our team described the removal of Zn(II), Fe(II) and Fe(III) from single-metal-ion chloride aqueous solutions with PIMs containing trihexyl(tetradecyl)phosphonium chloride (Cyphos IL 101) or trihexyl(tetradecyl)phosphonium bis (2,4,4trimethylpentyl)phosphinate (Cyphos IL 104) as metal ion carriers [6][7][8] and showed that Cyphos IL 101 is a more effective carrier of Fe(III) than of Zn(II). Kogelnig et al 9 reported that Zn(II) was efficiently extracted from 5 mol L -1 HCl using PIMs based on PVC matrix and Cyphos IL 101 as a carrier.…”
Section: Introductionmentioning
confidence: 99%